Analysis of Binary Cluster Interactions with Gaia DR2 - Naufal, Abdurrahman
Two star clusters can be located near each other as a result of either simultaneous birth or system encounters, and thus are called a binary cluster system. There are various cluster separation criteria used by studies in order to determine the bina- rity of a pair of clusters. Studies of binary clusters in Magellanic Clouds classied two clusters with projected separation < 20 pc as a binary cluster (e.g., Bhatia & Hatzidimitriou 1988), while in studies of Galactic binary clusters have used physical separation < 30 pc (de la Fuente Marcos & de la Fuente Marcos 2009) or 100 pc and velocity dierence of < 20 km s????1 (Conrad dkk. 2017). In this research, a list of Galactic binary cluster candidates is compiled from the open cluster catalogue by Cantat-Gaudin dkk. (2018), which is based on Gaia DR2. The criterion adopted by this work is the pair's physical separation must be less than 50 pc. With this criterion, 66 pairs are found; some of which have more than one neighbour identied. From the list, three candidate pairs were chosen to be analysed further: ASCC 16{ASCC 21, NGC 6716{Collinder 394, dan NGC 2547{Pozzo 1. Each pair has physical separation of 13 pc, 13 pc, and 46 pc. For each cluster, membership analysis and isochrone tting are done to estimate its age and photometric mass. The pairs ASCC 16{ASCC 21 and NGC 6716{Collinder 394 are found to be coeval with ages 10 Myr and 126 Myr respectively, while NGC 2547 and Pozzo 1 are found to be 25 and 13 Myr old respectively. For ASCC 16{ ASCC 21 and NGC 6716{Collinder 394, the separation between each cluster in the respective pairs is close enough to be interacting binary, while the wide pair NGC 2547{Pozzo 1 is not. Analysis of tangential kinematics of ASCC 16{ASCC 21 dan NGC 6716{Collinder 394 also shows that each pair may be gravitationally bound.